Life Skills Learning Strategies for Sewing Household Items in an Effort to Improve the Family Economy - Latiifa Mutiara Putri; Syuraini Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research is motivated by the successful implementation of life skills learning to sew household linen in an effort to improve the family economy in the Mega Permai Complex in Padang Sarai District, which is thought to be due to an effective learning strategy. This study aims to describe the learning strategies, learning approaches, methods and techniques of learning household linen sewing skills. This type of research is a qualitative research using a case study approach. Sources of data in this study consisted of research subjects, namely people who worked as tailors at the Mega Main Complex in Kel. Padang Sarai and research informants, namely owners and employees of sewing houses who produce household linen, and former employees who later set up their own businesses in the Mega Permai Complex. The data collection technique used the observation method, the interview method and the documentation method with the data analysis, namely data reduction, data presentation and drawing conclusions. Researchers in this study used triangulation techniques in order to assess the validity of the data. The results of this study indicate that: 1) the learning strategy used by educators as well as household linen sewing house owners is to use direct learning strategies. Because in learning activities it is more educator-centered and is most often used. And this learning strategy uses the lecture method and there is also an element of practice. 2) The learning approach used by educators as well as household linen sewing house owners is to use an individual approach. The individual approach is suitable because employees have different backgrounds. 3) The methods and techniques used by educators as well as household linen sewing house owners are using lecture and experimental learning methods and techniques..Keywords: Life Skills, Strategies, Approaches, Learning Methods and Techniques